2022
DOI: 10.1111/os.13187
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Multiplex PCR Assay for the Diagnosis of Prosthetic Joint Infections in the Routine Setting

Abstract: Objective: To evaluate the usefulness of a multiplex polymerase chain reaction (PCR) assay as a complementary tool in the diagnosis of prosthetic joint infections in the routine setting of a clinical microbiology laboratory, with a special focus on patients at high risk of culture-negative infections and high suspicion of infection. Methods:The results obtained in the routine care setting with the use of the commercial multiplex PCR (Unyvero i60©, Curetis AG, Holzgerlingen, Germany) were retrospectively review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our previous study (Jacobs et al, 2021) showed a high specificity and negative predictive value (NPV) and a low sensitivity and positive predictive value (PPV) for the mPCR Unyvero ITI G2 system. Diagnostic properties of this mPCR system were analysed by numerous other studies, reporting an excellent specificity ranging from 90 % to 100 %, indicating a positive result being truly positive with high probability (Metso et al, 2014;Hischebeth et al, 2016;Morgenstern et al, 2018;Sigmund et al, 2019Sigmund et al, , 2020Suren et al, 2020;Lüdemann et al, 2022;Auñón et al, 2022). However, the same studies reported a low sensitivity, ranging from 40 % to 80 %, meaning that a negative result does not exclude infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study (Jacobs et al, 2021) showed a high specificity and negative predictive value (NPV) and a low sensitivity and positive predictive value (PPV) for the mPCR Unyvero ITI G2 system. Diagnostic properties of this mPCR system were analysed by numerous other studies, reporting an excellent specificity ranging from 90 % to 100 %, indicating a positive result being truly positive with high probability (Metso et al, 2014;Hischebeth et al, 2016;Morgenstern et al, 2018;Sigmund et al, 2019Sigmund et al, , 2020Suren et al, 2020;Lüdemann et al, 2022;Auñón et al, 2022). However, the same studies reported a low sensitivity, ranging from 40 % to 80 %, meaning that a negative result does not exclude infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies did not even report any diagnostic values (Borde et al, 2015;Malandain et al, 2018;Zannoli et al, 2021;Auñón et al, 2022) or only mentioned the sensitivity of the mPCR (Villa et al, 2017;Aamot et al, 2019). In addition, the type of sample being analysed was different amongst studies: four studies analysed sonicate fluid (Hischebeth et al, 2016;Prieto-Borja et al, 2017;Zannoli et al, 2021;Auñón et al, 2022), two studies analysed tissue alone (Borde et al, 2015;Aamot et al, 2019), two studies analysed dithiothreitol (DTT) eluate (Villa et al, 2017;Zannoli et al, 2021), and most studies analysed synovial fluid alone (Lausmann et al, 2017;Sigmund et al, 2019;Suren et al, 2020;Lausmann et al, 2020;Jacobs et al, 2021;Lüdemann et al, 2022) or in combination with other aforementioned samples (Hischebeth et al, 2016;Villa et al, 2017;Malandain et al, 2018;Auñón et al, 2022;Lafeuille et al, 2021). Furthermore, there was a difference in the type of joint aspirated in each study, whereas in almost every case the hip and knee joint were aspirated, and occasionally, the shoulder, elbow, ankle, or spine were aspirated.…”
Section: Discussionmentioning
confidence: 99%
“…The samples selected for processing will be selected with close relationships with multidisciplinary teams, looking for patients with a probable diagnosis of PJI with a high pretest index of suspicion. We have recently published our clinical experience with this approach [71], showing that the number of patients that can benefit from a molecular test is high, even in a routine setting and not an experimental one (Figure 1). We need more reports about the experience of the laboratories in the use of molecular tests for PJI to select the best protocol to obtain the best results with the incorporation of these methods in the routine setting.…”
Section: How Can We Use These Methods?mentioning
confidence: 99%